Preferences for Redistribution among Emigrantsfrom a Welfare State - Ilpo Kauppinen; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
This paper studies attitudes towards income redistribution in the country of originamong those who stay in a welfare state, and those who emigrate. We find a strikinggender difference among Danish emigrants. Majority of men opposes increasing incomeredistribution, while majority of women supports it. Women are somewhat more positivetowards redistribution also in Denmark, but the gender difference is much smaller.We study to what extent differences in attitudes towards redistribution are driven bybeliefs about the determinants of individual success, generalized trust, assimilation tothe new home country, and self-selection of emigrants to the United States and otherdestinations. We do not find evidence of assimilation to political values prevalent in thenew home country.
Keywords: F22; J61; H20; 330; Migration; emigration; welfare state; redistribution; political preferences; Auswanderung; Sozialstaat; Dänemark; Einwanderung; Einkommensumverteilung; Meinung; Geschlecht; USA